When starvation challenges the tradition of niche conservatism: On a new speciesof the saxicolous genus Phymaturus from Patagonia Argentina withpseudoarboreal foraging behaviour (Iguania, Liolaemidae) - Scolaro, José Alejandro; Ibargüengoytía, Nora Ruth; Pincheira-Donoso, Daniel (Zootaxa, 2008)
The genus Phymaturus is known on the basis of almost twenty species with clear tendency to conserve saxicolous or terrestrial, and herbivorous niche. In this work, we present the description of a remarkable new Phymaturus species, Phymaturus agilis, with the peculiar ability to climb on large shrubs to feed on fresh flowers and fruits. This new species is a member of the Phymaturus patagonicus clade, restricted to Patagonia Argentina. Phymaturus agilis occurs at about 1100m of elevation in a volcanic rocky plateau close to Ingeniero Jacobacci, in the south western area of Rio Negro Province, Argentina. Comparative analyses conducted on morphological and coloration traits revealed substantial differences from Phymaturus spectabilis, the only Phymaturus species living in sympatry with P. agilis. Individuals of both species had recently been recognized as members of a single taxon with broad phenotypic variation.